2023
DOI: 10.1039/d2sc06559b
|View full text |Cite
|
Sign up to set email alerts
|

First-principles surface reaction rates by ring polymer molecular dynamics and neural network potential: role of anharmonicity and lattice motion

Abstract: Elementary gas-surface processes are essential steps in heterogeneous catalysis. A predictive understanding of catalytic mechanisms remains challenging due largely to the difficulties of accurately characterizing of the kinetics of such...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…87 Another new development in this eld has been the emergence of RPMD methods for describing gas-surface dynamics, such as recent work by Guo and coworkers, 88 who have studied H 2 dissociative chemisorption on Ag (111) and Pt (111), where this trajectory-based approach provides an easy way to study quantum effects related to tunneling over the dissociative barrier. Also, Li et al 89 have used RPMD to determine the rate of desorption of NO from Pd (111), where it is possible to include anharmonic effects and barrier re-crossing in the dynamics.…”
Section: High-dimensional Quantum Dynamicsmentioning
confidence: 99%
“…87 Another new development in this eld has been the emergence of RPMD methods for describing gas-surface dynamics, such as recent work by Guo and coworkers, 88 who have studied H 2 dissociative chemisorption on Ag (111) and Pt (111), where this trajectory-based approach provides an easy way to study quantum effects related to tunneling over the dissociative barrier. Also, Li et al 89 have used RPMD to determine the rate of desorption of NO from Pd (111), where it is possible to include anharmonic effects and barrier re-crossing in the dynamics.…”
Section: High-dimensional Quantum Dynamicsmentioning
confidence: 99%
“…By doing this, NQEs, such as tunneling and ZPE conservation, are included at a reasonable increase of cost (generally 1–2 orders of magnitude compared to QCT). RPMD has been successfully applied to, e.g., gas phase reactions, hydrogen diffusion on and NO desorption from metal surfaces, , water, and H atom scattering from graphene . Furthermore, the RPMD approach has also been used to simulate the DC of H 2 on Cu(111) and D 2 O on Ni(111), where it was observed that RPMD can accurately reproduce wave packet QD .…”
mentioning
confidence: 99%
“…Surface reactions present additional challenges due to the large number of surface DOFs. So far, some applications of the RPMD approach have been reported for surface processes, but none has been applied to chemical reactions in which bond breaking and bond formation are present.…”
mentioning
confidence: 99%